Geometric design projects for highways an introduction - Schoon, John G. 1937- (ASCE Press, 2000)
Introduces the geometric design of rural highways with an emphasis on basic specifications, approaches to preliminary route selection, alignment, drainage, cost, and environmental concerns. The second edition is based on metric units, expands on environmental reporting concerns, and adds computerized alignment modeling. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Highway engineering.; Roads -- Design and construction.; elektronické knihy; electronic books